Access to primary healthcare services and associated factors in urban slums in Nairobi-Kenya - Peter O. Otieno; Elvis O. A. Wambiya; Shukri M. Mohamed; Martin Kavao Mutua; Peter M. Kibe; Bonventure Mwangi; Hermann Pythagore Pierre Donfouet (BMC, 2020)
Abstract Background Access to primary healthcare is crucial for the delivery of Kenya's universal health coverage policy. However, disparities in healthcare have proved to be the biggest challenge for implementing primary care in poor-urban resource settings. In this study, we assessed the level of access to primary healthcare services and associated factors in urban slums in Nairobi-Kenya. Methods The data were drawn from the Lown scholars' study of 300 randomly selected households in Viwandani slums (Nairobi, Kenya), between June and July 2018. Access to primary care was measured using Penchansky and Thomas' model. Access index was constructed using principal component analysis and recorded into tertiles with categories labeled as poor, moderate, and highest. Generalized ordinal logistic regression analysis was used to determine the factors associated with access to primary care. The adjusted odds ratios (AOR) and 95% confidence intervals were used to interpret the strength of associations. Results The odds of being in the highest access tertile versus the combined categories of lowest and moderate access tertile were three times higher for males than female-headed households (AOR 3.05 [95% CI 1.47-6.37]; p < .05). Households with an average quarterly out-of-pocket healthcare expenditure of ≥USD 30 had significantly lower odds of being in the highest versus combined categories of lowest and moderate access tertile compared to those spending ≤ USD 5 (AOR 0.36 [95% CI 0.18-0.74]; p < .05). Households that sought primary care from private facilities had significantly higher odds of being in the highest versus combined categories of lowest and moderate access tertiles compared to those who sought care from public facilities (AOR 6.64 [95% CI 3.67-12.01]; p < .001). Conclusion In Nairobi slums in Kenya, living in a female-headed household, seeking care from a public facility, and paying out-of-pocket for healthcare are significantly associated with low access to primary care. Therefore, the design of the UHC program in this setting should prioritize quality improvement in public health facilities and focus on policies that encourage economic empowerment of female-headed households to improve access to primary healthcare.